NEW FIND OF STEGODON SOMPOENSIS MAXILLA FROM CANGKANGE, SOPPENG, SOUTH SULAWESI - Unggul Prasetyo Wibowo; Budianto Hakim; Andi Muhammad Saiful (WalennaE, 2019)
AbstractSulawesi is an island located in the Wallacean region of Indonesia. Geologically its lying midway between the Asian (Sunda) and Greater Australian (Sahul) continents. As a part of Wallacea islands, Sulawesi is an island that shows complexity either in biology or geology perspective. Though the distinctive quaternary vertebrate faunas has been described from Sulawesi,  historical pattern of biogeography still poorly understood due to the lack of the fossil specimens. This paper describes a maxilla fragment with molar root teeth M1 from an archaic proboscidae called Stegodon that found in the conglomeratic sandstone layer, at Cangkange Area, 4 km to the east of Cabenge Archeological site of South Sulawesi, Indonesia. Based on the comparation measuring data between this specimen with the Stegodon sompoensis and the Stegodon trigonocephalus it can be concluded that this Stegodon maxilla fragment is belong to the Stegodon sompoensis, a dwarf Stegodon from Sulawesi Island. The specimen is a surface collected sample. Based on the attached matrix on the maxilla fragment,  this specimen interpreted to be derived from subunit A of Beru Member, Walanae Formation. This Stegodon sompoensis is likely to be lived near the coastal-lagoon around 2,5 million years ago or Late Pliocene to Early Pleistocene. This estimated specimen age is based on the vertebrate fauna biostratigraphy of South Sulawesi. ABSTRAKPulau Sulawesi di Indonesia terletak di daerah Wallacea. Secara geologi pulau ini berada di antara Asia (paparan Sunda) dan Australia (paparan Sahul). Sebagai bagian dari kepulauan Wallacea, Pulau Sulawesi merupakan pulau yang memiliki kompleksitas baik dari segi biologi maupun geologinya. Meskipun fauna-fauna vertebrata kuarter Sulawesi sudah dideskripsi, tetapi sejarah dan pola biogeografi di pulau ini masih sangat kurang dikarenakan sedikitnya fosil-fosil yang ditemukan. Tulisan ini mendeskripsikan fragmen maxilla dari gajah purba jenis Stegodon dengan akar gigi molar M1 yang ditemukan di perlapisan batupasir konglomeratan, di daerah Cangkange, sekitar 4 km ke arah timur dari situs arkeologi Cabenge, Sulawesi Selatan, Indonesia. Berdasarkan  perbandingan data pengukuran spesimen ini dengan Stegodon sompoensis dan Stegodon trigonocephalus maka disimpulkan bahwa fragmen maksila Stegodon ini berasal dari Stegodon sompoensis, jenis Stegodon kerdil dari Pulau Sulawesi. Spesimen ini merupakan temuan permukaan, tetapi berdasarkan matriks sedimen yang masih menempel di maxilla, spesimen ini diinterpretasikan berasal dari Anggota Beru subunit A. Stegodon sompoensis ini diperkirakan dahulu hidup di lingkungan lagoon dekat pantai pada sekitar 2,5 juta tahun yang lalu atau Pliosen Akhir sampai Pleistosen Awal. Penentuan umur ini didasarkan pada boistratigrafi  fauna vertebrata  Sulawesi Selatan.